Hybrid optical communications for supporting the Palapa Ring network - Ucuk Darusalam; Fitri Yuli Zulkifli; Purnomo Sidi Priambodo; Eko Tjipto Rahardjo (Bulletin of Electrical Engineering and Informatics, 2020)
In order to connecting villages in rural area with a city, a hybrid optical communication is proposed. The Optical fiber communications that are implemented as a backbone on the Palapa Ring network has an opportunity to be expanded to reach rural area through the implementation of free-space optical communications (FSO) as the optical relaying networks (ORN). The major problem of FSO as the ORN is turbulence effects induce an optical propagation. In this research, FSO as the ORN implements novel technique to improve the performance of hybrid FSO where the amplification of signal is produced through serial configuration of optical amplifiers in cascaded meanwhile to reduce the noise in the end of receiver, optical band pass filter is implemented. The simulation of hybrid FSO is performed in Optisystem 7.0 where ORN is implemented in two nodes. The length of optical fiber connection to FSO is set to be constant at 75 km. The range of optical propagation in FSO is set at 1–9.4 m. The results of simulation show that at the range of 1–8 Km of optical propagation under atmospheric turbulence, range values for SNR and BER are achieved at 46.23–26.61 dB and 6.7x10-17–1.5x10-6, respectively.